On the Acheulean origin of mind and language - De Sá-Saraiva, Rodrigo; De Sá-Saraiva, Ana Isabel (Theoria et Historia Scientiarum, 2012)
Finally, we would like to restate that this paper is an exercise in thinking about what archaeological data mean in terms of cognition. As we said at the beginning, a more complex integration between theory of cognition and archaeological data is needed. This paper is a tentative step in that direction. As new data will be published, it may be that many of the archaeological features we attribute to the Late Acheulean are found to be more ancient. That would mean that the timetable we are proposing would have to be changed, and probably that the conclusions about the kind of language present would have to be modified. But, we hope, it would not harm the links between broad psychological concepts and patterns of archaeological data that we are proposing.